Pengaruh Proses Pengolahan dan Penyangraian Biji Terhadap Aktivitas dan Kandungan Senyawa Antioksidan Sari Kedelai Hitam Mallika (Glycine Max) - Rahayu, Wahidah Mahanani; Astuti, Erna (Universitas Ahmad Dahlan, 2017)
Black soybean roasting at certain temperature and period was reportedly able to increase its antioxidant activity. This research aimed to evaluate black soybean antioxidant properties after processed into soybean milk. After roasting at 200oC for 30 minutes, roasted and non-roasted black soybean were water-soaked for 12 hours. Soaked beans from both treatments were divided into two parts. First part was steamed for 30 minutes then ground with room temperature water. The second was not steamed but ground with 80oC water addition. After filtration, soybean milk was subjected to antioxidant activity, total phenolics, total flavonoids, and anthocyanin content analyses. Steamed-roasted soybeans milk had the highest antioxidant activity of 43.608%, but it contained significantly lower phenolics, flavonoids, and anthocyanin than non-roasted beans. Total phenolic compounds, flavonoids, and anthocyanin content of roasted beans were 37.99 â 33.8%, 15%, 16.57 â 27.53% lower than those of non-roasted beans, compared in steamed and hot-water added milk. Generally, milk from non-steamed and hot water added beans had higher total phenolics and flavonoids than those from steamed beans, while anthocyanin content remained higher in steamed soybean milk. The results suggested that there was other compounds which responsible on roasted beans antioxidant activity, other than phenolic compounds, flavonoids, and anthocyanin. Comparison of soybean milk processing method indicated than steaming was able to preserve non-phenolics and non-flavonoid antioxidative compounds generated during roasting, whereas 80oC water addition without steaming might optimize phenolics and flavonoids compound extraction.